SUSTAINABILITY INDICATORS FOR TOURISM SMES: APPLICATION TO PORTUGUESE CONTEXT - Sara Silveira; José Ramos; Oscar Silva; Fernando Almeida (Enlightening Tourism: A Pathmaking Journal)
Tourism has been a fundamental pillar for the development of the Portuguese economy and has supported and stimulated new opportunities. However, for small and medium enterprises (SMEs) in the hospitality sector, and given their specific characteristics, there are no specific indicators to monitor sustainability, and they are only based on existing generic models such as ETIS, WTO, and Green Globe. Given the complexity of the indicators in these models and their comprehensive vision, it makes it difficult for hospitality SMEs that have limited resources to measure them. Consequently, it is important to focus their attention on the most relevant indicators for their activity. In this sense, this study is relevant in identifying the critical sustainability factors for Portuguese hospitality SMEs. In total, and after the synthesis and assessment of the various indicators, a total of 35 critical indicators were identified, distributed among the economic, social, sustainable management, and environmental dimensions.